The role of microendodontics in the treatment of difficult cases such as C-shaped orifice of mandibular second molar with 5 canals - Peeters, Harry Huiz (Padjadjaran Journal of Dentistry, 2008)
Finding the incidence of anatomical variation in root canals is commonly found as a result of more sophisticated diagnostic tools. Therefore, a thorough understanding of the normal anatomy of canals and its variations in root canal treatments would be helpful in achieving the desired result. Usual root configuration of a mandibular second molar is two separate roots, distal and mesial, with one canal each. The incidence of a distinct 4 root canal in the distal root of C- shaped orifices is a rare phenomenon that is reported in the literature. This case study shows how to locate and manage a rare anatomical variation of a mandibular second molar with a distinct 4 canal in the distal aspect in a C-shaped orifice successfully, the successful treatment of this case explains that we should have an awareness and understanding of the presence of additional canals and abnormal morphology of the canals. Beside that the operatorâs perseverance and patience as well as sophisticated diagnostic tools such as the dental operating microscope, ultrasonic tips have an important role in treating unusual configurations of canals.